Social impacts of climate change in Mexico: A municipality level analysis of the effects of recent and future climate change on human development and inequality - Lykke E. Andersen; Dorte Verner (Institute for Advanced Development Studies (INESAD), 2010)
This paper uses municipality level data to estimate the general relationships between climate, income and child mortality in Mexico. Climate was found to play only a very minor role in explaining the large differences in income levels and child mortality rates observed in Mexico. This implies that Mexico is considerably less vulnerable to expected future climate change than other countries in Latin America.
Keywords: Q51; Q54; O15; O19; O54; 330; Climate change; social impacts; Mexico; Klimaveränderung; Soziale Folgen; Gemeinde; Mexiko